Metabolic Profiling Identified a Novel Biomarker Panel for Metabolic Syndrome-Positive Hepatocellular Cancer - Cao, Lin-Lin; Han, Yi; Wang, Yuanxiao; Pei, Lin; Yue, Zhihong; Qin, Li; Liu, Boyu; Cui, Jingwen; Jia, Mei; Wang, Hui (Frontiers in Endocrinology, 2022)
Metabolic syndrome (MetS) is an independent risk factor for hepatocellular cancer (HCC). Currently, there is no highly sensitive and specific biomarkers for HCC surveillance in MetS population. Metabolomics has been reported as a powerful technology for biomarker discovery. In the present study, we aimed to explore novel biomarkers with high sensitivity and specificity for MetS-positive [MetS(+)] HCC by metabolomic analysis. At first, many serum metabolites were found dysregulated in MetS(+) HCC individuals. Validation of the dysregulated metabolites by targeted metabolite analyses revealed that serum L-glutamic acid, pipecolic acid and 7-methylguanine were increased in MetS(+) HCC compared to MetS group. Then a biomarker panel including L-glutamic acid, pipecolic acid and alpha-fetoprotein (AFP) was identified as a novel biomarker for the diagnosis of MetS(+) HCC, with an area under the ROC curve (AUC) of 0.87 for discriminating MetS(+) HCC from MetS group. The biomarker panel was capable of detecting small (AUC = 0.82) and early-stage (AUC = 0.78) tumors as well. Moreover, it exhibited great diagnostic performance (AUC = 0.93) for discriminating MetS(+) HCC from other MetS-associated cancers, including colorectal cancer and gastric cancer. Collectively, our study establishes a novel diagnostic tool for MetS(+) HCC.